Caribbean Faith-Based Organisations: Friend or Foe in the fight against the feminisation of HIV and AIDS in the Anglophone Caribbean - Hem-Lee-Forsyth, Dr. Shivaughn; Thomas, Renee (Advances in Social Sciences Research Journal, 2021)
The feminisation of HIV and AIDS has become a worldwide phenomenon, and the Caribbean region has not been fortunate enough to be excluded. Caribbean females had 3-4 times higher infection rates than males up to a decade ago. Studies that focus on the contributing psychosocial factors to HIV risk in the Caribbean are limited. This narrative review showcases pivotal work which addresses the reciprocally connected responsibilities of patriarchy and religious practices and how they feed into the desolate reality of Anglophone Caribbean women. The relationship between these cultural issues in the Caribbean, using an anthropological lens, sets a platform for an investigation into HIV and AIDS. This paper seeks to encourage further research centred on the religious elements, which influence heterosexual relationships, and how these relationships are predisposed to potential HIV and AIDS risk. The ultimate goal of this study is to provide English- speaking Caribbean faith-based organisations, public health officials and policymakers a public stage to consider further policy implications for the staggering and disproportionate rates of HIV and AIDS between women and men.